Impact of Demographics, Loan Limits, and Borrowing Patterns on Debt Literacy in Bharatpur (BIC Journal of Management, 2025)
Debt literacy, a crucial aspect of financial literacy, measures the ability of individuals to understand the technical and contractual issues relevant to debt. This study, “Impact of Demographics, loan limit and borrowing patterns on Debt Literacy in Bharatpur”, describes the debt literacy among the borrowers at Bharatpur Metropolitan City, Nepal and examines the impact of demographics, loan limit and borrowing pattern. Despite the growth in access to formal credits as presented by United Nation Capital Development Fund & International Finance Corporation (2023), there is significant gap in academic research that discusses on how well the borrowers understand the terms and conditions associated with the debt agreements that they agreed to get credit facility. This study examines the impact of education qualification, age, gender, professional status, monthly income, residential status, subscribed loan limit and borrowing pattern (multiple banking) on debt literacy of borrowers at Bharatpur Metropolitan City, Nepal. This study adopts quantitative research approach using structured set of survey questionnaires and simple random sampling to collect data from 100 borrowers. Descriptive Statistics was used to reach to the debt literacy score. Regression analysis has been used to examine the impact of demographics, loan limit, and borrowing pattern on debt literacy. The result from descriptive statistics shows a mean score of 2.51 for debt literacy hinting many borrowers are unaware or lacks confidence in their understanding of debt related issues. Regression analysis showed that education qualification, professional status and gender have significant positive impact on the debt literacy of borrowers. To improve the borrowers’ debt literacy, campaigns relevant to debt literacy should be organized targeting non-professionals, borrowers with lower educational qualifications, and female borrower.